THE EFFECT OF MAP LIBS TECHNIQUE ON STUDENTS’ ENGLISH LEARNING ACHIEVEMENT IN LEARNING PERSONAL PRONOUN - Asti Veto Mortini; Aswadi Jaya; M. Ali Akbar Zam (Universitas PGRI Palembang, 2023)
The objectives of this study are to find out whether or not; (1) There is a significant effect of Mad Libs technique on Students’ Learning Achievement in Learning Personal Pronouns (2) There is a significant contribution of the Mad Libs technique on Students’ Learning Achievement in Learning Personal pronouns? This research used factorial experimental designs. These designs are essentially modifications of either the posttest-only control group or pretest-posttest control group designs. The sample was the students of PGRI University of Palembang. Two classes were chosen in which first class was experimental with male students was applied and the second was the second experimental group trained by Mad Libs with female students. The results showed that the First, Mad Libs technique affected the students’ learning achievement in learning Personal Pronoun at PGRI University. The result of t independent test was the mean of the experimental group was higher than the mean of the control group. It could be concluded; the experimental group and control group were significantly different and the Mad Libs technique was effective to use in improving students’ achievement in learning personal pronouns. Second, there was an interaction effect of the Mad Libs technique and students’ learning achievement toward achievement in learning personal pronouns.